Informational Support of the Investment Process in a Large City Economy - Chargazia, Tamara Zurabovna; Popova, Irina Vitalievna (Economy of Regions, 2016)
Large cities possess a sufficient potential to participate in the investment processes both at the national and international levels. A potential investor’s awareness of the possibilities and prospects of a city development is of a great importance for him or her to make a decision. So, providing a potential investor with relevant, laconic and reliable information, the local authorities increase the intensity of the investment process in the city economy and vice-versa. As a hypothesis, there is a proposition that a large city administration can sufficiently activate the investment processes in the economy of a corresponding territorial entity using the tools of the information providing. The purpose of this article is to develop measures for the improvement of the investment portal of a large city as an important instrument of the information providing, which will make it possible to brisk up the investment processes at the level under analysis. The reasons of the unsatisfactory information providing on the investment process in a large city economy are deeply analyzed; the national and international experience in this sphere is studied; advantages and disadvantages of the information providing of the investment process in the economy of the city of Makeyevka are considered; the investment portals of different cities are compared. There are suggested technical approaches for improving the investment portal of a large city. The research results can be used to improve the investment policy of large cities.